In-vitro diffusion study of ibuprofen-ï¢-cyclodextrin inclusion complex nanogel - Fitrianti Darusman; Debby Prihasti Ayustine; Saadiya Noerman; Sani Ega Priani; Widad Aghnia Shalannandia (Pharmaciana, 2021)
The inclusion complex is one way to enhance active substance solubility, affecting medicine dissolution and penetration. The inclusion complex is formed by utilizing b-cyclodextrin as the host of the active compounds. The Ibuprofen (2-(4-isobutyl-phenyl)propionate) is a propionate acid derivative and classified in class II of the Biopharmaceutic Classification System, which has low dissolutions and high permeability. This study aims to develop a nanogel containing ibuprofen-Î²-cyclodextrin inclusion complex with the ratio of 1:1, 1:2 and 2:1; and to compare the in-vitro diffusion profile with pure ibuprofen gel. The inclusion complex of ibuprofen-Î²-cyclodextrin was prepared using the coprecipitation method with the three molar comparison ratio of 1:1, 1:2, and 2:1. The in-vitro study was performed using the gel-based viscolam, comparing the three formulas of ibuprofen-Î²-cyclodextrin with pure ibuprofen gel. The ibuprofen concentration of each gel tested in the experiment was 1%. The particle size characterization of ibuprofen-Î²-cyclodextrin inclusion complex gel resulted in having nanoparticle size (510 nm). This characteristic indicates that the inclusion complex gel could enhance the cumulative release amount of ibuprofen compared with pure ibuprofen gel with a relatively smaller particle size (156 nm). Pure ibuprofen and inclusion complex powder size measured to be 763 nm and 957 nm, respectively. The ibuprofen-b-cyclodextrin inclusion complex gel with a molar ratio of 2:1 demonstrated an increase in in-vitro diffusion profile of ibuprofen with a cumulative release amount of 740.3 Âµg.cm-2. Meanwhile, pure ibuprofen gel had the cumulative release amount of 294.74 Âµg.cm-2. The gel containing ibuprofen-Î²-cyclodextrin inclusion complex could enhance the cumulative release amount of ibuprofen compared to pure ibuprofen gel. The ibuprofen-Î²-cyclodextrin inclusion complex gel at a ratio of 2:1 exhibited an increase in the diffusion of ibuprofen in-vitro.